2011
DOI: 10.1007/s11242-011-9857-z
|View full text |Cite
|
Sign up to set email alerts
|

A Water Retention Curve Model for the Simulation of Coupled Thermo-Hydro-Mechanical Processes in Geological Porous Media

Abstract: This paper presents a new water retention curve (WRC) model for the simulation of coupled thermo-hydro-mechanical processes in geological porous media. The model simultaneously considers the impact of porosity and temperature on suction, for both wetting processes and drying processes. The model is based on an idealization of porous geological media as having an isotropic and homogeneous microscopic pore structure. Suction is expressed as a function of degree of saturation, porosity, surface tension of the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Pore Water Pressure. Although the soil pore structure is composed of nonuniform pore size and the pore distribution is quite complex, most soils can be assumed to be a continuous, isotropic, and homogeneous porous medium, in which the distributions of pore water and air are also isotropic and homogeneous at a macroscopic scale [29]. Therefore, on per unit area of two-dimensional (2D) cross-section cutting through the soil for any angle, the total pore area A p , pore gas area A g , and pore water area A w are constant.…”
Section: Derivation Of the Porosity-dependent Swrc Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Pore Water Pressure. Although the soil pore structure is composed of nonuniform pore size and the pore distribution is quite complex, most soils can be assumed to be a continuous, isotropic, and homogeneous porous medium, in which the distributions of pore water and air are also isotropic and homogeneous at a macroscopic scale [29]. Therefore, on per unit area of two-dimensional (2D) cross-section cutting through the soil for any angle, the total pore area A p , pore gas area A g , and pore water area A w are constant.…”
Section: Derivation Of the Porosity-dependent Swrc Modelmentioning
confidence: 99%
“…An elliptical pore randomly distributes on arbitrary cross-section. Each pore contains an identical elliptic air bubble (Figure 1(b)) [29]. The total normal force of a given crosssection is expressed as…”
Section: Derivation Of the Porosity-dependent Swrc Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…One, based on surface tension-viscous flow theory [11,12], states that a change in temperature affects only the surface tension. For example, Philip and de Vries [13] established a relationship between suction and temperature change based on the Laplace equation, and Wang et al [14] and Tong [15] derived the effect of temperature on a SWCC model theoretically. However, the results of later experiments gradually revealed the insufficiency of this view, as they indicated that the effect of temperature on the capillary pressure of unsaturated soil cannot be attributed solely to its effect on surface tension [4,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%